2021
DOI: 10.5709/acp-0316-x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Reviewer Profile Photo on Purchase Decision: Evidence from Event-Related Potentials

Abstract: Although the number of studies on online reviews is growing, the impact of reviewer photo on consumer purchase decision-making has not yet been examined systematically. In particular, the underlying neural mechanisms have remained underexplored. Thus, the present study investigated whether and how reviewer photos affects consumers to make a purchase decision by using event-related potentials (ERPs). At the behavioral level, participants demonstrated a higher purchase rate with a shorter RT in situations with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…As we expected, P2, N2, and P3 components were successfully elicited in our results. Based on the visual observation of the grand-averaged ERPs waveforms and past research on purchase decisions ( Ma et al, 2008 ; Gajewski et al, 2016 ; Jin et al, 2020 ; Tang and Song, 2021 ), five electrodes (F3, F4, FC1, FC2, and Fz) were selected for P2 and N2 analysis, and five additional electrodes (CP1, CP2, P3, P4, and Pz) were chosen for the P3 analysis. The P2 was analyzed as the peak amplitude in the time window of 130–200 ms after onset.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As we expected, P2, N2, and P3 components were successfully elicited in our results. Based on the visual observation of the grand-averaged ERPs waveforms and past research on purchase decisions ( Ma et al, 2008 ; Gajewski et al, 2016 ; Jin et al, 2020 ; Tang and Song, 2021 ), five electrodes (F3, F4, FC1, FC2, and Fz) were selected for P2 and N2 analysis, and five additional electrodes (CP1, CP2, P3, P4, and Pz) were chosen for the P3 analysis. The P2 was analyzed as the peak amplitude in the time window of 130–200 ms after onset.…”
Section: Methodsmentioning
confidence: 99%
“…For example, negative framing messages automatically mobilized more attentional resources and induced a larger P2 amplitude than positive framing messages ( Jin et al, 2017 ). Furthermore, situations with reviewer photos would recruit more attentional resources and induce a larger P2 amplitude than situations without reviewer photos ( Tang and Song, 2021 ). According to regulatory fit, consumers would devote more attentional resources to the cognitive processing of product information when the task at hand matched with individuals’ regulatory focus ( Higgins, 2000 ; Lee and Aaker, 2004 ; Cesario and Higgins, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…To be specific, a longer RT generally suggests a higher decision difficulty and cognitive load (Tang & Song, 2021; Wang et al, 2016). For instance, Tang and Song (2021) engaged subjects in an online purchase task with different reviewer photo conditions and noted a shorter RT for the with-reviewer photo condition (vs. without-reviewer photo condition), indicating that the with-reviewer photo condition was perceived to be more favorable to the participants. In line with previous research, the differences in the RT might suggest that subjects might exert extra cognitive load to complete the decision task in the default position condition (vs. personalized position condition) because of the higher decision difficulty.…”
Section: Discussionmentioning
confidence: 99%
“…ERPs method has been adopted by more and more scholars for consumer behavior research that mainly focuses on product, branding, pricing, and advertising (Alsharif et al, 2023; Goto et al, 2019; Guo et al, 2016; Ozkara & Bagozzi, 2021; Wang et al, 2023; Yu et al, 2022). Based on ERPs components, such as N400 and late positive potential (LPP), scholars have studied different marketing strategies (Jai et al, 2021; Jin et al, 2017; Tang & Song, 2021). Therefore, behavioral and ERPs methods were adopted to investigate the effect of review position type on consumers’ purchase intentions.…”
mentioning
confidence: 99%
“…Existing research has indicated that response time was associated with cognitive load. Higher cognitive load means a longer response time (Cowen et al, 2002; Leuthold et al, 2011; Tang & Song, 2021). It took participants much longer time to respond to the purchase decisions when expert reviews and consumer reviews are conflictive.…”
Section: Discussionmentioning
confidence: 99%